“Did I look at the blackness, or did I look at the stars?” The role of spirituality in mental health and recovery - Milner, Katja (2023)
Spirituality in both religious and non-religious forms is an important component of mental health and recovery. Research demonstrates that many people would like to have their spiritual needs addressed within mental healthcare services. However a ‘spirituality gap’ exists in the difference in value placed on spirituality by professionals compared with service users, often resulting in people’s spiritual needs being neglected or poorly understood within clinical practice. A recovery approach to mental health care seeks to value and better understand lived experience. Supporting clinicians to better understand spirituality from the perspectives of people who experience mental health difficulties could help to bridge the spirituality gap and improve spiritual care within mental health services.